(untitled) - Woolf, Murray B. (New York, 2007)
A comprehensive review that gives you insight into the latest innovations in network-based project planning, scheduling, and control…saving you time and money on all construction projects. Faster Construction Projects with CPM Scheduling contains a full explanation of the new and innovative Scheduling Practice Paradigm, and translates it into tangible steps you can use to create powerful project schedules designed to boost productivity on any job. Completely compatible with the Collaborative Model, the new Scheduling Practice Paradigm provides, commitment planning, execution scheduling, and comprehensive performance control.
Keywords: Building,Critical path analysis,Production scheduling,Xây dựng,Xây dựng qui trình sản xuất; Superintendence,Sự giám sát; Phân tích điểm tới hạn